Peripheral Intravenous Access in Preterm Neonates during Postnatal Stabilization: Feasibility and Safety - Baik-Schneditz, Nariae; Pichler, Gerhard; Schwaberger, Bernhard; Mileder, Lukas; Avian, Alexander; Urlesberger, Berndt (Frontiers in Pediatrics, 2017)
Background: Current European Guideline for resuscitation recommends a centrally positioned umbilical venous catheter (UVC) as the best option for administering necessary drugs. Especially in preterm infants, a frequently used alternative is the peripheral venous catheter. Methods: Two randomized controlled studies were conducted at the Division of Neonatology, Medical University of Graz. During neonatal resuscitation, a standardized protocol was filled out by an uninvolved observer including time points after birth of all attempts of venous puncture, time point of successful venous puncture and total number of needed attempts. Arterial oxygen saturation (SpO2) and heart rate (HR) were measured using pulse oximetry at the right hand/wrist. In each neonate either NIRO 200NX (Hamamatsu, Japan) or INVOS 5100C (Covidien-Medtronic, USA) were used to measure cerebral tissue oxygenation index (cTOI) and cerebral regional oxygen saturation (crSO2), respectively. SpO2, HR, cTOI/crSO2 during and 1 minute before and after successful venous punctures were analysed. Results: 70 protocols were reviewed. Data of 61 preterm neonates were analysed. Mean gestational age was 31.5 ± 2.2 weeks and the mean birth weight was 1527 ± 541 grams. In median, it needed one attempt (IQR 1-2) to establish a peripheral venous catheter. In median IV catheterization was successfully established 5 (IQR 4-9) minutes after birth. SpO2 and cTOI/crSO2 rose significantly following the percentiles during the first 10 minutes after birth. Heart rate did not change significantly. Conclusion: In conclusion, peripheral IV catheterization during postnatal stabilisation of preterm infants is feasible and successful in most of the cases at first attempt.